Una comedia polychrónica: juegos de la temporalidad en Plutos de Aristófanes - Fernandez, Claudia N. (Letras Clássicas, 2003)
Ancient Comic Genre handles time development with extreme freedom. In Aristophanes Plutus, the framework of different temporalities, in other words, the different perceptions of time in the bosom of the drama, confirms the freedom we have just mentioned and contributes to the construction of the contradictory meanings of the comedy. Nevertheless, the utopian time of Chronos’ Age finally dominates, and the comedy expresses the disappointment of the author, who cannot find another relief than the no-time of the myth.